Drug Utilization Study in a Tertiary Care Hospital of Tribal Area in South India - Ajay M. Khade; Jyoti A. Khade; M. Shakeel M Bashir (Technological Innovation in Pharmaceutical Research Vol. 10, 2021)
Due to the irrational use of drugs, we are facing numerous problems of overuse, misuse, increased cost, antibiotic resistance etc. The present study was conducted in a tertiary hospital in which the patients are referred from surrounding rural and tribal areas. It is a retrospective study that included the patients admitted in clinical departments. A total of 200 patients (Males 41.5% and Females 58.5%) were included and their case records were reviewed. Most of the patients belong to age group < 30 years. The average No. of drugs per prescription was 4.76.Intravenous route was commonly used. The dose of the drug was inappropriate in 38% patients and inappropriate frequency in 3% cases. It was found that the most commonly prescribed group of drugs was antimicrobial agents (41.53%) with Ampicillin (53.01%) as the most commonly prescribed antimicrobial agent. Culture and Sensitivity was not conducted in any of the patient. Single antimicrobial agent was prescribed in 42% cases and combination of 2 antimicrobial agents in 38% cases. Thus, the drug utilisation in patients included in the study is not rational and hence, many recommendations were suggested.